Team Whoosh Generator 2013 WSGC Collegiate Rocket Competition - Pajunen, Kirsti; Johnson, Eric; Larson, Chris; Falcon, Victoria; Ihrcke, James (Proceedings of the Wisconsin Space Conference, 2014)
The objective of the 2013 Wisconsin Space Grant Consortium Collegiate Rocket competition was to design, build, and launch a single-stage high powered rocket that must reach a target altitude of 3000 feet and deploy a parachute(s) electronically for a successful recovery. Upon recovery, the rocket must be determined to be in a flyable condition to be considered a successful launch. Teams receive a launch score based on their combination of reaching the desired altitude and on whether or not the rocket was recovered in a flyable condition. At the kick-off meeting, Team Whoosh Generator was informed they would be using a Cesaroni I540 motor and a 4.0-in airframe diameter. An RRC2 mini altimeter (from last yearâ€™s rocket) and an ALTS25 altimeter given to the team at this yearâ€™s altimeter conference were selected to complete the apogee requirements. Upon reaching apogee (estimated around 3080 feet) a drogue chute deployed under which the rocket descended until it reached an altitude of 500 feet. A second chute then deployed such that a slow decent speed was obtained for landing. A Transolve Beep-X Sonic Locator was activated before launch and was used to aid in recovery of the rocket. Included in this report are design details considered, anticipated performance, photos of the construction process, and flight results. 1Â